Blueberries - Retamales, J. B. (Jorge B.) (Crop production science in horticulture ;, 2012)
Blueberry cultivation has increased dramatically as production has shifted into new regions. Blueberries are now widely available as food and also processed to be used in medicine and pharmaceuticals for their antioxidant properties. This new and practical book covers the major topics of interest to blueberry breeders and researchers including botany, physiology, nutrition, growth regulation, photosynthesis, environment, weeds, pests, diseases and postharvest management. The main focus is on the most important cultivated species, the highbush blueberry, although information on other blueberries and related species is also provided. It is an essential resource for soft fruit researchers, extension workers, academics, breeders, growers, and students.